Development of Questionnaires for Measuring Pregnancy Anxiety, Sleep Quality, Knowledge Level, and Birth Readiness - Jannah, Nurul; Selvarajh, Gunavathy (International Journal of Nursing Information, 2024)
Assessing the health of pregnant women with a questionnaire can prevent complications and help health professionals provide appropriate care. Assessment scales such as the pregnancy anxiety rating scale questionnaire (PARSQ), pregnancy sleep quality questionnaire (PSQQ), pregnancy knowledge level questionnaire (PKLQ), and birth readiness questionnaire (BRQ) need to be developed according to current conditions and real-life situations to serve as primary screening tools before proceeding with further treatment for pregnant women. This study aims to develop specific research measurement tools for pregnant women and validate the PARSQ, PSQQ, PKLQ, and BRQ questionnaires. The research method employed a qualitative approach by distributing questionnaires to 20 pregnant women, followed by statistical testing of questionnaire validity and reliability. The results showed that the calculated values (r-value) for the PARSQ, PSQQ, PKLQ, and BRQ questionnaires were greater than the critical value (r-table) of 0.359, indicating that the items in these four questionnaires are valid. The reliability test results used Cronbach's alpha for all four questionnaires, indicating that the questionnaires are reliable. In conclusion, the PARSQ, PSQQ, PKLQ, and BRQ questionnaires can be used to detect the health conditions of pregnant women. This research's contribution, through the use of questionnaires, can offer an effective tool for collecting and analyzing data needed to understand the phenomenon of pregnancy and improve existing theories and practices. Further research is recommended with a larger sample size of pregnant respondents.